1991
DOI: 10.1002/eji.1830211135
|View full text |Cite
|
Sign up to set email alerts
|

The role of C5a and antibody in the release of heparan sulfate from endothelial cells

Abstract: The activation of endothelial cells is thought to contribute to the host response to infection and to the pathogenesis of autoimmune disease. It was recently shown that antibody and complement can activate endothelial cells leading to cleavage and release of heparan sulfate from the cells. We show here that release of heparan sulfate from endothelial cells is mediated by antibody and the complement fragment C5a and that assembly of the membrane attack complex and lysis of endothelial cells is not necessarily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 25 publications
2
66
0
2
Order By: Relevance
“…HS proteoglycans are rapidly released under conditions of inflammation and tissue damage (17)(18)(19). The release of HS is mediated by proteolytic cleavage of the protein core or by endoglycolytic cleavage of the HS chains (18,20).…”
mentioning
confidence: 99%
“…HS proteoglycans are rapidly released under conditions of inflammation and tissue damage (17)(18)(19). The release of HS is mediated by proteolytic cleavage of the protein core or by endoglycolytic cleavage of the HS chains (18,20).…”
mentioning
confidence: 99%
“…Structural modifications of the saccharide residues, especially sulfation, confer manifold biological activities, including regulation of cell adhesion, proliferation, development, anticoagulant, and chemical mediator functions (18 -21). Injury of tissues (22) or exposure of endothelial cells and, perhaps, other cells to activated complement or to neutrophils or platelets causes rapid cleavage and shedding of heparan sulfate proteoglycans and glycosaminoglycan fragments (23)(24)(25)(26). The release of heparan sulfate is postulated to be mediated by proteolytic cleavage of the protein core or by endoglycolytic cleavage of the heparan sulfate chains (25,(27)(28)(29).…”
mentioning
confidence: 99%
“…Various C fragments may participate in production of tissue pathology in hyperacute rejection. We found that C5a in conjunction with natural antibodies causes the cleavage and loss of heparan sulfate from the endothelium (12). The loss of heparan sulfate might contribute to disruption of blood vessel integrity and also to intravascular coagulation, which are components of hyperacute rejection.…”
Section: Discussionmentioning
confidence: 83%
“…Heparan sulfate release correlated with serum levels of IgM antibodies that bound to porcine endothelial cells and also with deposition of iC3b on the cells, but not with serum C activity (11). The loss of heparan sulfate was found to be triggered by C5a and natural antibody acting in combination on endothelial cells (12).…”
Section: Endothelial Cell Activation By Antibody and Complement: Relementioning
confidence: 85%